A Pink Slip for the Blue Reform: Is Selection, Experience, or Ideology the Elixir of Populists’ Survival? - Dehdari Sirus H.; Matakos Konstantinos; Meriläinen Jaakko; Tukiainen Janne (Now Publishers, 2022)
Why do some populist parties thrive while others fail or split? Is it possible for populists to maintain anti-establishment nature while being in a coalition with the mainstream parties? We study the populist Finns Party that split while being part of a coalition government. The splinter party Blue Reform retained its part in government and most of the experienced political personnel, yet it failed in the next election while the rump party remained popular. Leveraging rich data on electoral candidates and voters, we explore various potential drivers of the electoral persistence of populist parties: candidate quality, selection, office perks, and ideological motivations. Our results indicate that ideological proximity with voters and their demand for descriptive representation are keys for the electoral success of populist parties. This has implications for the political and policy consequences of including populists in government. In particular, our work highlights that there are limits on the electoral returns to ideological moderation, and that political experience and the perks of office alone do not guarantee populists’ survival.